Dimensions of security. Issue 2 (4th March 2019) - Hill, J. N. C.; Cavatorta, Francesco
Abstract: The Arab uprisings' failure to bring about either the scale or type of political change in the Maghreb that it initially seemed to promise belies the significance of its impact on the region. While Algeria, Mauritania and Morocco continue to be ruled by the same competitive authoritarian regimes that held power when the protests began, they, and the new governments in Tunisia and Libya, must now negotiate an altered and more dangerous security environment than before. The unsettling of Tunisia's security apparatus and the outbreak of full-blown civil war in Libya have created new opportunities for terror and criminal groups to thrive and expand. The primary aim of this special issue is to chart and explain many of the critical changes in the Maghreb's security environment that have occurred as a result of the Arab Spring. Each of the articles collected here identifies and analyses at least one important security issue in one or more Maghreb country as well as explain how that issue has emerged in response to or been affected by the Arab Spring.